Adult Oral Health Inequalities Described Using Area-based and Household-based Socioeconomic Status Measures - Lisa M. Jamieson, PhD; W. Murray Thomson, PhD (Blackwell Synergy, 2006)
To describe adult oral health inequalities using an area-based and household-based measure of socioeconomic status (SES).